2011 7th International Wireless Communications and Mobile Computing Conference 2011
DOI: 10.1109/iwcmc.2011.5982498
|View full text |Cite
|
Sign up to set email alerts
|

Outage optimum routing for wireless networks

Abstract: Abstract-A new routing metric for multi-hop wireless ad hoc networks is presented. The proposed metric is based on the computation of Signal-to-Noise Ratio (SNR) and minimization of wireless network outage probability in a fading environment. This metric improves the Quality-of-Service by reducing dropped packets. Further, by modeling the network with a Trellis diagram and then using Viterbi Algorithm to select the best routing path, we reduce the routing complexity of our approach. Simulation results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…From the simulations, the proposed method achieved higher throughput than the conventional routing protocol that used hop count as routing metric. In [20], routing selection was improved using minimum summation of the inverse SNR. The metric was equivalent to this method of all the links in the path.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…From the simulations, the proposed method achieved higher throughput than the conventional routing protocol that used hop count as routing metric. In [20], routing selection was improved using minimum summation of the inverse SNR. The metric was equivalent to this method of all the links in the path.…”
Section: Related Workmentioning
confidence: 99%
“…The use of SNR and Receive Power (RP) to find the route was proposed by [18,19] by adding up the SNR information into Route Reply (RREP) mechanism. In [20] and [21], routing selection was improved using minimum summation of inverse SNR and weighted SNR average of all links in the path, respectively. Moreover, a study reported in [22] proposed a routing protocol for wireless sensor networks through SNR-based dynamic clustering, while that reported in [23] used cooperative Automatic Repeat reQuest (ARQ) system to minimize total network energy consumption while delivering a minimum required SNR.…”
mentioning
confidence: 99%
“…Outage probability is an important parameter and has been considered as optimization criteria [18], [19]. For an application with outage probability requirement of P , one constraint which needs to be satisfied is P out ≤ P .…”
Section: Cross-layer Derivationmentioning
confidence: 99%
“…In the literature, the multi-hop RS problem has been mainly analyzed for relay networks with a single user [6]- [8]. In [6], the authors show that an efficient dynamic programming approach implemented at a central processor can find the optimal relay path by comparing the bottleneck-link signal-to-noise-ratios (SNRs) of each path.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the multi-hop RS problem has been mainly analyzed for relay networks with a single user [6]- [8]. In [6], the authors show that an efficient dynamic programming approach implemented at a central processor can find the optimal relay path by comparing the bottleneck-link signal-to-noise-ratios (SNRs) of each path. When compared to exhaustive search, for a single-user decode-and-forward (DF) relay network, the optimal RS can be found very efficiently based on this approach.…”
Section: Introductionmentioning
confidence: 99%